ANALISIS ITSM PADA LAYANAN PELATIHAN PADA APLIKASI PINTAR BY KEMENTERIAN AGAMA DENGAN MENGGUNAKAN METODE ITIL - Pransiska Adela Susilowati; Tata Sutabri (ADISAM PUBLISHER, 2024)
This research discusses the analysis of Information Technology-based Smart Kemenag application service management using the ITIL 3 framework. The research was conducted with the aim of increasing satisfaction with Smart Kemenag application services in smart Kemenag applications. The method used in this research is descriptive qualitative with data collection techniques through interviews and observation. The research results show that implementing the ITIL 3 framework in the Smart Kemenag application can improve ITSM service management. One of the widely known IT governance framework standards is ITIL. After conducting research, it was found that the Event Management variable obtained an average maturity level value of 4.85 and was included in maturity level 4, namely managed. In the Incident Management variable, the average maturity level value is 4.85 and is included in maturity level 4, namely managed. In the Management Problem variable, the average maturity level value was 4.86 and was included in maturity level 4, namely managed. In the Demand Fulfillment variable, the average maturity level value is 4,87 and is included in maturity level 4, namely managed. And for the Access Management variable, the average maturity level value is 4.41 and is included in maturity level 4, namely managed. Maturity level 4 is managed, which means the related processes have been planned and implemented routinely and documented using standards and process performance measurements have been carried out